Sea-level science : understanding tides, surges, tsunamis and mean sea-level changes - Pugh, David; Woodworth, Philip (Cambridge : Cambridge University Press, 2014)
Understanding sea-level processes, such as ocean tides, storm surges, tsunamis, El Niño and rises caused by climate change, is key to planning effective coastal defence. Building on David Pugh's classic book Tides, Surges and Mean Sea-Level, this substantially expanded, full-colour book now incorporates major recent technological advances in the areas of satellite altimetry and other geodetic techniques (particularly GPS), tsunami science, measurement of mean sea level and analyses of extreme sea levels. The authors discuss how each surveying and measuring technique complements others in providing an understanding of present-day sea-level change and more reliable forecasts of future changes. Giving the how and the why of sea-level change on timescales from hours to centuries, this authoritative and exciting book is ideal for graduate students and researchers in oceanography, marine engineering, geodesy, marine geology, marine biology and climatology. It will also be of key interest to coastal engineers and governmental policy-makers.
Preface -- List of acronyms -- List of main symbols -- Introduction -- Sea-level measuring systems -- Tidal forces -- Tidal analysis and prediction -- Tidal dynamics -- Shallow-water and coastal tides -- Storm surges, meteotsunamis and other meteorological effects on sea level -- Tsunamis -- Spatial variations in sea-level -- Mean sea-level changes in time -- Sea-level changes in time to do with the solid Earth -- Sea-level applications -- Sea level and life -- Appendix A. Basic hydrostatic and hydrodynamic equations -- Appendix B. Currents -- Appendix C. High and low water times and heights from from harmonic constituents -- Appendix D. Theoretical tidal dynamics -- Appendix E. Legal definitions in the coastal zone -- Glossary.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Sea level -- History; Ocean -- History